Explorar e investigar para aprender matemática por meio da modelagem matemática - Kfouri, William (2008)
This study aims at investigating whether Mathematical Modeling would be a viable way to the teaching and learning of mathematics in Basic Education, suggesting it as other possibility to address the contents of this matter. For that, a mini-course on this subject was implemented, for high school teachers, with the objective of influencing their teaching practice, in addition to disclosing, explaining and showing what is the teaching of mathematics through Modeling and the innovative ideas to create another learning environment. We also examine the connection and receptivity on the part of teachers, making them concerned with the implementation of Mathematics Modeling as part of the process of teaching / learning and advising on this strategy alternative. From real situations, of their daily lives and practices, this mini-course showed to the teachers the importance of mathematics to human knowledge and to understand the environment where they live We present some ways that the modeling can provide to make mathematics in the classroom different and attractive to their students. We also, would like to remove the stigma that mathematics is considered difficult by many, uninteresting by others and even inaccessible to most. We described in this work, the meetings and experiences developed with fiftyfive teachers, who recognized Modeling as a way to awaken in the students the interest for the study of mathematics, not only encouraging the teaching, but also the development of an open mind to research and new experiences. It is presented, as a conclusion, the activities developed of Modeling being employed in the teaching of Mathematics and on the ways to "make Mathematics" in the classroom